Proceedings of the 8th International Modal Analysis Conference, January 29 - February 1, 1990, Hyatt Orlando, Kissimmee, Florida - International Modal Analysis Conference (8th : 1990 : Kissimmee, Florida); Union College. Graduate and Continuing Studies; Society for Experimental Mechanics (Schenectady, NY : Union College, 1990)
09